# If x=2,y=6 is the solution of equation of 3ax + 2ay=6 then find value of b from 2(a-1)+ 2(3b-4)=4.

2
by KSA

Log in to add a comment

by KSA

Log in to add a comment

Substituting, 3a(2)+2a(6)=6

6a+12a=6

18a=6

a=6/18=1/3

Substituting value of a in 2(a-1)+2(3b-4)=4

2a-2+6b-8=4

2(1/3)-2+6b-8=4

(2/3)-2+6b=4+8

-4/3+6b=12

6b=12+4/3

6b=40/3

b=40/3x6

b=40/18

b=20/9

The Brainliest Answer!

3a(2)+2a(6)=6 ⇒ 6a+12a = 6 ⇒ 18a = 6 ⇒ a = 1/3

2(a-1) + 2(3b-4) = 4

2a - 2 + 6b - 8 - 4 = 0

2/3 - 14 + 6b = 0

6b - 40/3 = 0

6b = 40/3

b = 40/3 ÷ 6

b = 40/18

b = 20/9